Effectiveness of Trancutaneus Electrical Nerce Stimulation On Frozen Shoulder (TENS): Literatur Review - Rismayanti, Rismayanti; Hutabarat, Heny Agnesia; Alpiah, Dini Nur (International Journal of Social Research, 2024)
Frozen shoulder is shoulder joint pain that occurs at an average age of 40-70 years with a prevalence of 3% of the general population in Indonesia. Trangutansus Electrical Nerve Stimulation (TENS) is a therapeutic modality using electric current which is able to stimulate the nervous sytem. This research aims to determine the effectiveness of (TENS) in frozen shoulder sufferers. Literatur review research was carried out using PICO search in databases such as Googke Scholar. There were 4 journals that met the criteria and showed the results that TENS was carried out twice a week, with a duration of 10-15 minutes and applied in continuous mode for 1 month with a p-value<0.05 shows a significant effect on reducing pain when carrying out daily activities such as washing clothes, combing hair, and picking up items from high places. So the author can conclude that TENS is effective in reducing pain and can also increase the joint range of motion (ROM) in the shoulder